Holocene sedimentary facies in coastal plain of the Song Ma Delta, Thanh Hoa Province - Ha, Vu Van; Lam, Doan Dinh; Duong, Nguyen Thuy; Cuc, Nguyen Thi Thu; Quang, Nguyen Minh; Tha, Hoang Van; Min, Nguyen Thi; Tuan, Dang Minh; Tung, Dang Xuan; Chi, Giap Thi Kim (Vietnam Journal of Earth Sciences, 2019)
The Ma river delta located in the North Central of VietNam is the third largest ones in Vietnam following the Mekong Delta and the Red River Delta. However, there are not many researches on sedimentary. This study aims to determine the Characteristics of the Holocene sedimentary facies in coastal plain of the Song Ma Delta based on observation of sedimentary structure and analysis of grain size, diatom, flora, pollen and 14C dating collected for the drill core (LKTH2 borehole) from the coastal plain of the Song Ma river delta. Research results identify 08 facies consisting 02 facies of transgression period and 06 facies of regression period. During transgression period, 02 facies of tidal flat clayish silt and bay silty clay facies were formed. Of which, tidal flat clayish silt face was formed in 7,883 ± 43 14C yr BP. After the maximum flooding of the sea, the delta was initiated and 06 facies were formed during the regression period i.e. prodelta silty clay, delta front clayish silt, tidal flat sandy - silty clay, sand ridge, lagoonal sandy silty clay, and flood plain silty clay facies. The tidal flat sandy - silty clay facies occurred in 6.951± 38 14Cyr BP caused by sea level fall and the coastline was identified around the LKTH2 bore hole at that time. Integration of sedimentary facies of the sand ridge and lagoonal sandy silty clay facies shows that the Song Ma Delta was dominated by wave process during its evolution.